HYBRIDITY AND OTHERNESS IN ALGERIAN POSTCOLONIAL LITERATURE - Neema Ghenim (Universitas PGRI Madiun, 2020)
The paper considers the dualistic existence between the Self and the Other during the Great War. Algerian participation in the war was compulsory and many authors wrote about the event.: Albert Camus, a Frenchman who belonged to a pied-noir family, Mohamed Ben Chérif, an Arab from Djelfa, and Elissa Rhaïs, a Jewish writer from Blida. The First Man (1994), Camus’s book, deals with the French who were reluctant participants in war. Mohamed Ben Chérif also published his first book, Ahmed Ben Mostapha Goumier (1997) that represents those Algerians who sought friendship with the French. In Le Café Chantant (1920), Elissa Rhaïs gives another picture of an Algerian who participated in the Great War. This paper examines the meeting with the Other that left indelible marks on the protagonists’ identities.